Satellitome analysis illuminates the evolution of ZW sex chromosomes of Triportheidae fishes (Teleostei: Characiformes) - Kretschmer, Rafael; Goes, Caio Augusto Gomes [UNESP]; Bertollo, Luiz Antônio Carlos; Ezaz, Tariq; Porto-Foresti, Fábio [UNESP]; Toma, Gustavo Akira; Utsunomia, Ricardo; de Bello Cioffi, Marcelo (Springer Nature, 2022)
Satellites are an abundant source of repetitive DNAs that play an essential role in the chromosomal organization and are tightly linked with the evolution of sex chromosomes. Among fishes, Triportheidae stands out as the only family where almost all species have a homeologous ZZ/ZW sex chromosomes system. While the Z chromosome is typically conserved, the W is always smaller, with variations in size and morphology between species. Here, we report an analysis of the satellitome of Triportheus auritus (TauSat) by integrating genomic and chromosomal data, with a special focus on the highly abundant and female-biased satDNAs. In addition, we investigated the evolutionary trajectories of the ZW sex chromosomes in the Triportheidae family by mapping satDNAs in selected representative species of this family. The satellitome of T. auritus comprised 53 satDNA families of which 24 were also hybridized by FISH. Most satDNAs differed significantly between sexes, with 19 out of 24 being enriched on the W chromosome of T. auritus. The number of satDNAs hybridized into the W chromosomes of T. signatus and T. albus decreased to six and four, respectively, in accordance with the size of their W chromosomes. No TauSat probes produced FISH signals on the chromosomes of Agoniates halecinus. Despite its apparent conservation, our results indicate that each species differs in the satDNA accumulation on the Z chromosome. Minimum spanning trees (MSTs), generated for three satDNA families with different patterns of FISH mapping data, revealed different homogenization rates between the Z and W chromosomes. These results were linked to different levels of recombination between them. The most abundant satDNA family (TauSat01) was exclusively hybridized in the centromeres of all 52 chromosomes of T. auritus, and its putative role in the centromere evolution was also highlighted. Our results identified a high differentiation of both ZW chromosomes regarding satellites composition, highlighting their dynamic role in the sex chromosomes evolution.
Keywords: FISH; Fishes; High-throughput sequencing; satDNA evolution; Satellitome; Sex chromosome evolution